ANALISIS PENGARUH ORIENTASI KEWIRAUSAHAAN DAN KOMPETENSI PENGETAHUAN TERHADAP KAPABILITAS UNTUK MENINGKATKAN KINERJA PEMASARAN (STUDI EMPIRIK PADA INDUSTRI PAKAIAN JADI DI KOTA ROGOJAMPI KABUPATEN BANYUWANGI) - Dani Dwi Astuti (UNEJ e-Proceeding)
This research is done by taking research object at small scale handmade clothes industry in Rogojampi, amounting to 170 company with its population element that is manager/owner. Sampling technique that used is purposive sampling. Amount of determined responder as research sample is 100 people. Analysis technique that used to interpret and analyze data in this research is technique of Structural Equation Model (SEM) of software package of AMOS. Result of examination proven hypothesis that factor entrepreneurial orientation and knowledge of market become positive effect of marketing capability and marketing performance. It is mean high significance of each other variables. As for model which is raised in this research can be accepted posed at by index according to where value of GFI 0,900, value of chi-square 87,987, probability value 0,084, value of TLI 0,965 and value of CFI 0,973, all have up to standard although value of AGFI 0,853 accepted by marginal.